2020
DOI: 10.3390/molecules25030695
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Improvement of Stability and Conductivity of Hybrid Composites formed by PEDOT:PSS and SnO Nanoparticles

Abstract: In this work, layered hybrid composites formed by tin oxide (SnO) nanoparticles synthesized by hydrolysis and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) have been analyzed. Prior to the composite study, both SnO and PEDOT:PSS counterparts were characterized by diverse techniques, such as X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM), photoluminescence (PL), atomic force microscopy (AFM), optical absorption and Hall effect measurements. Special atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…TEM observations ( Figure 1 a) confirmed the presence of nanoparticles and plates, as described in a previous work [ 8 ]. Jaśkaniec et al [ 16 ] recently suggested that solvent polarity on the synthesis method is strongly related to these 2D morphology changes.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…TEM observations ( Figure 1 a) confirmed the presence of nanoparticles and plates, as described in a previous work [ 8 ]. Jaśkaniec et al [ 16 ] recently suggested that solvent polarity on the synthesis method is strongly related to these 2D morphology changes.…”
Section: Resultssupporting
confidence: 88%
“…Jaśkaniec et al [ 16 ] recently suggested that solvent polarity on the synthesis method is strongly related to these 2D morphology changes. As an example, SnO can be obtained as platelets [ 8 , 17 ], rose-like particles [ 13 , 25 , 26 ], and other hierarchical architectures [ 9 , 10 ]. In our case, both plates and nanoparticles morphologies were formed via hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart than biomedical field, other applications of composite nanoparticles are photovoltaics and space missions. The improved photovoltaic performance of nanocomposite materials was demonstrated by Vázquez-López et al by the synthesis of hybrid systems of SnO nanoparticles and conductive poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonate [ 9 ]. On the other hands, Winroth et al reported the structure and performance of multifunctional polymer matrix composites composed of ultrahigh molecular weight polyethylene fiber reinforcement and a hydrogen-rich polybenzoxazine matrix, demonstrating clear advantages over benchmark materials in terms of combined structural and radiation-shielding performance [ 10 ].…”
mentioning
confidence: 99%